The Influence of Education, Health, and Income Inequality on Poverty: Panel Data Evidence from Regencies and Municipalities in Jambi Province - Amri, Khairul; Fitri, Cut Dian; Bakar, Jariah Abu (Jurnal Prajaiswara, 2024)
Introduction/Main Objective: Poverty remains a significant challenge for local governments in achieving economic development goals in Jambi Province. To address this issue, local governments have undertaken efforts to improve the quality of education and healthcare. Additionally, development initiatives are expected to enhance income distribution within society. This study aims to examine and analyze the effects of education and healthcare on poverty reduction in Jambi Province. Unlike previous studies, this research incorporates the Gini ratio as a predictor variable for poverty rate. Research Methodology: The data utilized in this study are secondary data obtained from the Central Bureau of Statistics of Jambi Province. The data comprise panel data from 11 regencies and cities for the period 2011–2023. The analytical model employed is panel regression using the fixed-effects approach. Findings/Results: The study reveals that education and healthcare have a significant and negative impact on poverty rate. Improved education and healthcare quality are associated with lower poverty rate. Conversely, income inequality, has a significant positive effect on poverty, where an increase in the Gini ratio leads to higher poverty rate. Conclusion/Recommendations: Poverty rate in Jambi Province are significantly influenced by the quality of education and healthcare, as well as income inequality. Therefore, local governments in Jambi Province should implement integrated and actionable policies by simultaneously intervening in the areas of education, healthcare, and income distribution.